MAQASID SYARI’AH FI AL- AZAN: DIRASAH TAHLIILIYAH MIN KHILALI MAHIYAH WA SYURUT AL-AZAN FI AL-MAZAHIB AL-ARBA’AH - Zaenal Abidin Mochamad Baqir (IAIN Surakarta, 2019)
This article aims to find out the essence of the call to prayer by analyzing the definition, conditions, pillars of prayer, and the history of asbab al-nuzul the call to prayer itself. because the call to prayer is the teachings of religion that characterizes Islam in all corners of the world. This research is important to find out the essence of azan so that afterward there are no mistakes on the azan procedure because mistakes on the azan procedure will cause the essence of the adzan to be realized. This article is new in the field of the Shariah maqosheed because the author discusses the adhan specifically from all perspectives to find all the maqosheed in it, because one case in the shari'ah may have several maqosheed contained therein. Likewise, this paper is expected to be able to open the door for other researchers in the field of sharia, in examining other parts besides the call to prayer and exposing their Shariah maqosheed.